2022
DOI: 10.1051/0004-6361/202243900
|View full text |Cite
|
Sign up to set email alerts
|

ulisse: A tool for one-shot sky exploration and its application for detection of active galactic nuclei

Abstract: Context. Modern sky surveys are producing ever larger amounts of observational data, which makes the application of classical approaches for the classification and analysis of objects challenging and time-consuming. However, this issue may be significantly mitigated by the application of automatic machine and deep learning methods. Aims. We propose ULISSE, a new deep learning tool that, starting from a single prototype object, is capable of identifying objects sharing the same morphological and photometric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…In this section, we summarize four out of the five "solutions" submitted to the DC (since one using CNNs and transfer learning has been already been presented by Doorenbos et al 2022). One submission used a non-ML method that extended the traditional approach based on color-color diagrams by adding magnitude standard deviation and the coefficients of correlation between light curves in two wave bands.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we summarize four out of the five "solutions" submitted to the DC (since one using CNNs and transfer learning has been already been presented by Doorenbos et al 2022). One submission used a non-ML method that extended the traditional approach based on color-color diagrams by adding magnitude standard deviation and the coefficients of correlation between light curves in two wave bands.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we find that 64 × 64 pixel image cutouts are not sufficient for extracting pixel-level information. However, in the parallel effort done on low-redshift/low-luminosity AGNs (Doorenbos et al 2022), it was found that images of resolution 224 × 224 pixels can be used to directly extract meaningful information that can help in disentangling AGNs from non-AGN hosts. Moreover, the quality of images in all six bands that will be provided by LSST will allow us to develop DL models for separating AGNs from galaxies in a highly efficient manner at the cost of additional computing power.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations